Dyskusje teoretyczno literackie na przełomie XX i XXI wieku = Debate on literary theory at the turn of the 20th and 21st centuries - Heck, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study is to present an overview of the promising literary theory after poststructualism.This paper mentions the return to literary studies of such categories as subjectivity (an author),evaluation and textual meaning. This article deals with polemics against deconstruction, feminism,new historicism shading some light on the tension between institutional frames of contemporaryliterary theory and the intellectual interest in nonconformist investigations into literature. The authorargues that it is currently possible to combine the tradition of philology with the cutting edgeliterary research.
Keywords: teoria literatury; literaturoznawstwo